2019
DOI: 10.1002/adfm.201807901
|View full text |Cite
|
Sign up to set email alerts
|

A Unified View on Nanoscale Packing, Connectivity, and Conductivity of CNT Networks

Abstract: The design of functional structures from primary building blocks requires a thorough understanding of how size, shape, and particle-particle interactions steer the assembly process. Specifically, for electrically conductive networks build from carbon nanotubes (CNTs) combining macroscopic characterization and simulations shows that the achievable conductivity is mainly governed by CNT aspect ratio, length dispersity and attractive interactions. However, a direct link between the actual 3D network topology that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…[93] Of course, the filler-matrix interaction needs to be sufficiently strong to enable an acceptable degree of dispersion quality. [94][95][96][97] It is further recommended to verify the impact on other macroscopic properties. [75,[98][99][100][101] It has been additionally indicated that the extrudate swell is influenced by the filler shape as well.…”
Section: Effect Of Polymer Materials Parametersmentioning
confidence: 99%
“…[93] Of course, the filler-matrix interaction needs to be sufficiently strong to enable an acceptable degree of dispersion quality. [94][95][96][97] It is further recommended to verify the impact on other macroscopic properties. [75,[98][99][100][101] It has been additionally indicated that the extrudate swell is influenced by the filler shape as well.…”
Section: Effect Of Polymer Materials Parametersmentioning
confidence: 99%
“…Recent work on three-dimensional morphological quantification 45,46 and modeling of CNS reinforced polymers 47,48 has shown that a significant amount of stochastically-varying local curvature is exhibited by the CNSs present in the polymer matrix. 45 These works also show that such structural randomness leads to the formation of a large number of van der Waals dominated junctions that may contribute to the mechanical and transport properties of such architectures.…”
Section: Introductionmentioning
confidence: 99%
“…3D descriptions of CNS morphologies in nanocomposites have recently been provided using quantitative electron tomography 45,46 and small angle X-ray scattering. 50 Specifically, we have developed an electron tomographic Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the option to model I-V curves, either macroscopically or in C-AFM, it will be clear that full details on the complete path between the one electrode (or tip) and the other electrode are required, which so far have not been obtained. Simulations with an effective (constant) contact resistance, taking the various pathways into account as done for carbon nanotube composites [32], will thus be (highly) approximate, as shown in this paper for CB composites, because the contact nature (and area) will vary considerably. We note that papers dealing with the electrical conduction of carbonaceous particulate polymer composites (see, e.g., refs.…”
Section: General Considerationsmentioning
confidence: 99%